PENDIDIKAN PRANIKAH DALAM MEMBENTUK KELUARGA SAKINAH, MAWADDAH, WARRAHMAH - Elva Fahrun; Yoyo Hambali; Musyaffa Amin Ash Shabah (Al-Ihsan: Journal of Community Development in Islamic Studies, 2023)
The marriage desired by all prospective husbands and wives is a sakinah, mawaddah, warrahmah marriage, but in practice the road to marriage often experiences various obstacles and leads to divorce. Cases of divorce or divorce lawsuits continue to increase every year, a factor indicating this phenomenon is caused by various factors such as economic conditions, the environment, the presence of infidelity, the unpreparedness of a candidate to domestic violence. The solution for handling this case is by providing guidance on premarital education as an implementation of the readiness of the prospective husband and wife to get married. This activity is a form of student service to the community in the Real Work Lecture program with the Community Education method, namely using a socialization approach, mentoring or monitoring and providing webinars as exposure to premarital education and community consultation. The results of this activity are expected to be able to overcome problems that occur in the community and minimize the level of divorce to domestic violence in the community.